âPrototype Poster HIV/AIDS untuk PSK Dolly dan Jarak di Kecamatan Sawahan Kota Surabaya Berdasar Teori P-Processâ - Siswantara, Pulung (Jurnal PROMKES, 2015)
Prostitution area is known to be one of many causes of the growing number of HIV/AIDS patients inSurabaya. Abdi Asih foundation has done several attempts to prevent this, but so far have not been able to successfully deliver the key idea to the intended audience. This calls for a more comprehensive and accurate method to the sex workers to improve their HIV/AIDS consciousness and knowledge level.The objective of this research is to improve the existing HIV/AIDS information poster media. The improvement process is implemented based on the steps suggested by the P-Process theory.Â Â Â Â Â Â Â Â Â This is an observational research with cross-sectional design which uses both quantitative and qualitative methods. Quantitative approach was used to know the knowledge. Qualitative approach was applied by using FGD and in-depth interview with the commercial sex workers as the respondents.The result of this research shows that respondentsâ knowledge about HIV/AIDS is considerably low. The Wilcoxon Sign Rank Test yields a probability score of 0.03 which indicates that this new poster media is indeed effective in improving the respondentsâ knowledge and consciousness about HIV/AIDS issues.Based on the research result, it can be concluded that the poster media prototype has been found to be effective in improving respondentsâ knowledge about the mentioned issues, due to the fact. Suggesting for future improvement, it is better to give substantial consideration in audienceâs wishes and common characteristic in designing effective information poster media.